2023
DOI: 10.3390/microorganisms11010113
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Strategies to Control Campylobacter at Different Stages of the Food Chain

Abstract: Campylobacter is one of the most common bacterial pathogens of food safety concern. Campylobacter jejuni infects chickens by 2–3 weeks of age and colonized chickens carry a high C. jejuni load in their gut without developing clinical disease. Contamination of meat products by gut contents is difficult to prevent because of the high numbers of C. jejuni in the gut, and the large percentage of birds infected. Therefore, effective intervention strategies to limit human infections of C. jejuni should prioritize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 211 publications
0
30
0
Order By: Relevance
“…Campylobacter jejuni poses a serious threat to public health and currently there are no available antibacterial solutions to eliminate this pathogen through the food production chain (20). Here, we exploit the target specificity of phages and the killing efficiency of pyocins to develop novel antibacterials against C. jejuni.…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter jejuni poses a serious threat to public health and currently there are no available antibacterial solutions to eliminate this pathogen through the food production chain (20). Here, we exploit the target specificity of phages and the killing efficiency of pyocins to develop novel antibacterials against C. jejuni.…”
Section: Discussionmentioning
confidence: 99%
“…To successfully combat Campylobacter at farm level, it is necessary to prevent and impede introduction into poultry flocks, the transmission, colonization, and to reduce its overall prevalence 5 . Results of previous studies indicate that individual measures may not be sufficient to control Campylobacter 6 , 7 . For this reason, it has been suggested that a combination of multiple strategies might be beneficial 3 , 8 , 9 , a new control strategy summarized under the term “multiple-hurdle approach” .…”
Section: Introductionmentioning
confidence: 96%
“…Preharvest control of Campylobacter in poultry production is a critical step in order to reduce carcass contaminations during processing and subsequent foodborne transmission [24,25]. However, poultry houses can be contaminated by Campylobacter in many different ways, making controlling Campylobacter in poultry a very challenging task [20].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple non-biosecurity measures (e.g., vaccines, bacteriocins, phages, feed additives, competitive exclusion products, etc.) have been evaluated to control Campylobacter in live birds with various outcomes [20,24,25,27,28]. Significant reductions in Campylobacter colonization in chickens were observed in several studies involving bacteriophages, various types of vaccines, and feed additives (29,30,31,32,33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation